2000
DOI: 10.1055/s-0037-1613926
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thrombotic Risk in Family Members of Unselected Individuals with Factor V Leiden

Abstract: SummaryThe factor V Leiden mutation (FVL) leads to a seven-fold increased risk of venous thromboembolism (VTE). In thrombophilic families, 25% of carriers have experienced thrombosis before the age of 40 years. Aim of our study was to assess the association of FVL with VTE in first-degree family members of unselected symptomatic and asymptomatic carriers of FVL.We tested 197 relatives of consecutive thrombosis patients with FVL and 36 relatives of asymptomatic carriers on the presence of FVL and the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 25 publications
5
49
0
3
Order By: Relevance
“…However, when the analysis was limited to the 273 kindreds whose proband had a first episode of venous thromboembolism, excluding those presenting with SVT or arterial thrombosis, the results did not substantially change. This finding is in agreement with a recent observation on a similar annual incidence of venous thromboembolism in carriers of factor V Leiden belonging to families whose probands had venous thromboembolism or were asymptomatic (Lensen et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…However, when the analysis was limited to the 273 kindreds whose proband had a first episode of venous thromboembolism, excluding those presenting with SVT or arterial thrombosis, the results did not substantially change. This finding is in agreement with a recent observation on a similar annual incidence of venous thromboembolism in carriers of factor V Leiden belonging to families whose probands had venous thromboembolism or were asymptomatic (Lensen et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…The absolute incidence of VTE ranged from 0.19%/year to 0.49%/year, compared with 0.05%/year to 0.10%/year in individuals without the mutation. 37,63,182,183 VTE occurred in 7-12% of relatives with Factor V Leiden heterozygosity, compared with 2-3% of relatives without the mutation, consistent with other estimates that the lifetime risk for thrombosis is approximately 10%. Multiple prospective cohort studies found a similar low incidence of VTE in asymptomatic Factor V Leiden heterozygotes, in the range of 0.1%/year-0.67%/year.…”
Section: Penetrancesupporting
confidence: 88%
“…35 The lifetime risk of VTE is higher (25-40%) in heterozygotes from thrombophilic families. 36,37 Heterozygosity for Factor V Leiden is not associated with an increase in mortality or reduction in normal life expectancy. 38,39 …”
Section: Natural History and Clinical Manifestationsmentioning
confidence: 97%
See 2 more Smart Citations